Halal practices for responsible production and consumption towards sustainable future - Aung, Tin Shine; Jasman, Winda; Alesandra, Junita; Johar, Hanawuri Nahari; Hidayati, Nurul; Ruslan, Mohd. Firdaus (IPB University, 2025)
Halal practices rooted in Islamic principles are offering a framework of ethical, social, and environmental responsibilities with modern sustainability efforts. Therefore, this research aims to explore the intersection of halal practices and sustainable development, focusing on responsible production and consumption to support environmental, social, and economic well-being. A qualitative method is used to analyze existing literature on halal practices, sustainability, and green marketing strategies, with case research from various industries implementing halal principles. These principles emphasize ethical agricultural and livestock farming, humane animal treatment, mindful consumption, and waste minimization, which resonate with the pillars of sustainability. Meanwhile, green marketing in halal industry catalyzes the promotion of environmentally friendly products and ethical consumer behavior, transcending religious boundaries and appealing to diverse markets. The integration of the principles into production and marketing strategies positions the industry as a model for sustainable and ethical practices due to increased global demand for halal-certified products. The results show that halal practices significantly contribute to sustainability across various industrial sectors by prioritizing social and environmental well-being. The potential of halal practices is reported to drive global sustainability and enhance a culture of responsibility across industries and consumer segments.